THERMAL INSULATING MATERIAL WITH HIGH MECHANICAL STRENGTH MADE FROM CLAY BRICK WASTE AND COAL ASH USING THE MICROWAVE ENERGY - LUCIAN PAUNESCU; MARIUS FLORIN DRAGOESCU; SORIN MIRCEA AXINTE (Journal of Engineering Studies and Research)
The paper presents the results of experimental research for manufacture a high mechanical strength thermal insulating material using the microwave energy. Clay brick waste (75 - 83 mass %) and coal ash (15 - 23 mass %) as raw material and silicon carbide (2%) as a foaming agent have been used as a powder mixture. The porous product obtained by a sintering/ foaming process at 1115 - 1145 ºC had relatively low density and thermal conductivity (0.50 - 0.68 g/cm3 and 0.078 - 0.095 W/mK, respectively) and high compressive strength (up to 7.5 MPa). This remarkable combination of some physical and mechanical characteristics of the insulating material allows its use in applications involving mechanical stress resistance.